The Role and Real Actions of Young Voters Post-2024 Simultaneous Elections - imran, imran; Ramadhani, Suci; Idharulhaq, Idharulhaq (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
This community service article examines the active role of young voters in North Lombok during and after the 2024 simultaneous elections, challenging prevailing narratives about youth political apathy. Based on participatory observation and discussion at the North Lombok Election Commission (KPU) podcast on November 28, 2025, this study documents how young people contributed significantly to electoral integrity through multiple roles including election organizers (KPPS and PPK), peace mediators, and sustained civic activists. The analysis employs the Sasak cultural philosophy of